Hybrid origin of European Vipers (Vipera magnifica and Vipera orlovi) from the Caucasus determined using genomic scale DNA markers. Issue 1 (December 2016) - Zinenko, Oleksandr; Sovic, Michael; Joger, Ulrich; Gibbs, H.
Abstract Background Studying patterns of introgression can illuminate the role of hybridization in speciation, and help guide decisions relevant to the conservation of rare taxa.Vipera magnifica andVipera orlovi are small vipers that have high conservation status due to their rarity and restricted distributions in an area of the Caucasus region where two other related species are present –V. kaznakovi andV. renardi. Despite numerous observations of hybridization between different species of small vipers, and the potential of a hybrid origin forV. magnifica andV. orlovi based on their distribution with respect toV. kaznakovi andV. renardi, hypotheses of a hybrid origin have not been formally tested. Here we generate genomic-scale data by performing next generation sequencing of double digest restriction-site associated DNA libraries, and use these multilocus data to test whether these two species are of hybrid origin. Results We generated over nine hundred loci for 38 specimens of six taxa, and analysed the dataset using Bayesian clustering and multivariate methods, as well as Patterson D-statistics, which can distinguish between incomplete lineage sorting and introgression as explanations for shared polymorphism. The results demonstrate a pattern of historical admixture in the two purported hybrids that is consistent with past gene flow fromV. renardi intoV. kaznakovi . The average admixture proportion in individuals was low (6.39 %) in the case ofV. magnifica, but was higher inV. orlovi (19.02 %). We also show that the specific individual samples used in D-statistic tests can have a significant impact on inferences regarding the magnitude of introgression, suggesting the importance of including multiple individuals in these analyses. Conclusions Our results support the conclusion that bothV. orlovi andV. magnifica had formed through a hybridization event betweenV. kaznakovi andV. renardi . Given a low proportion of admixture and absence of clear ecological and morphological differencesV. magnifica should be treated as a marginal population ofV. kaznakovi . Further studies that include analyses of ecological segregation ofV. orlovi from parental taxa and search for evolutionary consequences of hybridisation would clarify ifV. orlovi is a distinct hybrid species. Until this we recommend preserving the current taxonomy and protection status ofV. orlovi .